Variation of Aflatoxin Level in Different Poultry Feeds Used in Different Poultry Farms of Bangladesh Round the Year - Khan, M.M.H.; Chowdhury, B.; Bhuiya, M.R.H.; Rahim, M. (International Journal of Poultry Science, 2005)
As quality of feed is the main determinant factor in successful poultry farming attempts were made to evaluate the quality of feeds used in the farms of Bangladesh in respect of aflatoxin. Feed samples were collected from two layer farms, four big hatcheries and six broiler farms located in different areas of Bangladesh and the collection was continued for twelve months. In feed samples collected during the twelve months, aflatoxin content was found to vary from 0 to 98 ppb. Only aflatoxin B1 was detected in the feed samples and the percentage of incidence was at a maximum in the months of June, July and August, while and from November to February, no aflatoxin was detected in any feed. Higher amount of aflatoxin accumulation in the poultry feed was noticed in rainy season. A positive correlation (0.814) was found to exist between the moisture and aflatoxin contents of the feed. Feed used in the breeder farm was superior to those of broiler and layer farms with respect to aflatoxin content. Poor quality maize could be considered as a source of aflatoxin contamination in poultry feed as it contained reasonable amount of the toxin (23 to 121 ppb) irrespective of the season. Storage condition as practiced in the farm and the left-over feed of the farm might not have contributed to the elevation of aflatoxin level in poultry feed.